Metagenome-assembled genomes indicate that antimicrobial resistance genes are highly prevalent among urban bacteria and multidrug and glycopeptide resistances are ubiquitous in most taxa - Magnúsdóttir, Stefanía; Saraiva, Joao Pedro; Bartholomäus, Alexander; Soheili, Majid; Toscan, Rodolfo Brizola; Zhang, Junya; Nunes da Rocha, Ulisses; , CLUE-TERRA consortium (Frontiers in Microbiology, 2023)
Every year, millions of deaths are associated with the increased spread of antimicrobial resistance genes (ARGs) in bacteria. With the increasing urbanization of the global population, the spread of ARGs in urban bacteria has become a more severe threat to human health. In this study, we used metagenome-assembled genomes (MAGs) recovered from 1,153 urban metagenomes in multiple locations to investigate the fate and occurrence of ARGs in urban bacteria. Our results showed an alarming prevalence of multidrug and glycopeptide ARGs among urban bacteria. Additionally, we analyzed the deterministic effects of phylogeny on the spread of these ARGs and found that many ARG classes have a non-random distribution within the phylogeny of our recovered MAGs. Our results suggest that the observed non-random spreads of ARGs are not due to the transfer of plasmids and that most of the bacteria observed in the study are unlikely to be virulent. Additional research is needed to evaluate whether these ARG classes will become entirely prevalent among urban bacteria and how they spread among phylogentically distinct species.